2020
DOI: 10.1093/jxb/eraa319
|View full text |Cite
|
Sign up to set email alerts
|

High day and night temperatures distinctively disrupt fatty acid and jasmonic acid metabolism, inducing male sterility in cotton

Abstract: Abstract High temperature (HT) stress is an inevitable environmental factor in certain geographical regions. To study the effect of day/night HT stress on male reproduction development, the H05, a heat-sensitive cotton line, was subjected to HT stress. High day and Normal night (HN) and Normal day and High night (NH) temperature treatments were compared with control (Normal day and Normal night, NN). At the anther dehiscence stage, significant differences were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…Jasmonic acid is well-documented in biotic stress response regulation [ 2 ], for example, the defense of viral. However, current results also found that jasmonic acid is involved in the protective response against heat stress [ 14 , 15 ]. The molecular mechanism underlying heat stress response has been largely uncovered, and the gene regulatory network is still less addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonic acid is well-documented in biotic stress response regulation [ 2 ], for example, the defense of viral. However, current results also found that jasmonic acid is involved in the protective response against heat stress [ 14 , 15 ]. The molecular mechanism underlying heat stress response has been largely uncovered, and the gene regulatory network is still less addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, JA promotes programmed cell death by inducing ROS production and regulating leaf morphogenesis. It protects the plant's fertility under heat stress, while the content, synthesis, and signal transduction of JA are inhibited under heat stress [77][78][79][80][81]. Auxins reduce stress injury caused by high-temperature exposure through improving pollen fertility, thus, improving the crop yield [82][83][84][85].…”
Section: Phenotypic and Endogenous Hormone Pathways In Response To Hi...mentioning
confidence: 99%
“…Heat stress can cause damage to a cotton plant in almost every stage of its life, but it is reported that the reproductive stages of cotton are more sensitive to high temperature than compared to vegetative growth stages [15]. Both day and night temperatures play an important role in determining yield potential in crop plants, but high night temperature reduces yield and causes significant damage, while the role of high day temperature is secondary [16]. The adverse effects of high night/day temperature on different plant stages are shown in Figure 1.…”
Section: Effects Of High Temperature Stress On Cottonmentioning
confidence: 99%